The Effect of Air Pollution on The Stomata Characteristics Pigeon Orchid (Dendrobium crumenatum) Leaves, In the Tasikmalaya - Nofi rahma Isma yanti; Purwati Kuswarini Suprapto; Diki Muhamad Chaidir (Universitas PGRI Semarang, 2023)
This study aims to determine the effect of air pollution on the stomata characteristics in Pigeon Orchid (Dendrobium crumenatum) leaves in Tasikmalaya. This research is quantitative. The Samples were taken through survey method with purposive sampling technique in the Singaparna Bus Station as an exposed area with the highest air pollution, Sukaraja-Mangunreja street as an exposed area with the moderate air pollution, and Mount Galunggung as an exposed area with the the lowest air pollution. The characteristics of the stomata observed using an Optilab camera type Professional Model Series MTN001 which already has the Image Raster application and previously calibrated with an object glass micrometer at 400 x magnifications. The Data analysed quantitatively and descriptively using one way ANOVA test. The results showed that different levels of air pollution could affect the characteristics of the stomata. Stomata in areas with high air pollution have the highest stomata index and stomata density, namely 8.2% and 326.11/mm2, with the category of medium density and oval stomata shape. Stomata in areas with moderate air pollution have the lower stomata index and stomata density, namely 7.3% and 256.47/mm2, with the low-density category and round stomata shape. Meanwhile, stomata in areas with low air pollution have the lowest stomata index and stomata density, namely 5.7% and 256.47/mm2, which indicate the category of low density and the shape of the stomata is round.